The Influence of Work-Life Balance and Workload on Employee Performance at Bank BTN Tasikmalaya Branch Office - Rojab, Rafly Zulkia; Rahwana, Kusuma Agdhi; Asyiah, Ai Kusmiati (CV. Ulil Albab Corp, 2024)
This research purposse to determine and analyze the picture of work-life balance, workload and employee performance at Bank BTN Tasikmalaya Branch Office. The influence of work-life balance and workload on employee performance simultaneously at Bank BTN Tasikmalaya Branch Office. The influence of work-life balance on employee performance partially at Bank BTN Tasikmalaya Branch Office and the influence of workload on employee performance partially at Bank BTN Tasikmalaya Branch Office. The method used in this research is a survey with a descriptive approach. With a research sample of 35 collection department employees as respondents. The data used is primary and secondary data. The analytical tool used in this research is multiple linear regression using the SPSS version 26 support application. The test results show that work-life balance has a good classification, workload has a good classification and employee performance has a high classification, simultaneously showing the variables used. in the research, work-life balance and workload have a significant effect on employee performance at Bank BTN Tasikmalaya Branch Office. Partially, there is a significant influence of workload on employee performance, while work-life balance does not have a significant influence on employee performance.